2021
DOI: 10.1101/2021.10.23.462170
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compatibility logic of human enhancer and promoter sequences

Abstract: Gene regulation in the human genome is controlled by distal enhancers that activate specific nearby promoters. One model for the specificity of enhancer-promoter regulation is that different promoters might have sequence-encoded preferences for distinct classes of enhancers, for example mediated by interacting sets of transcription factors or cofactors. This biochemical compatibility model has been supported by observations at individual human promoters and by genome-wide measurements in Drosophila. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…While it has been demonstrated that using stronger promoters in MPRA helps to detect repressive elements, its sensitivity and specificity has not been evaluated systematically 8,27 . In addition, it has been demonstrated that interactions between CREs can exhibit specificity depending on context including the cell-type and TFs involved 28,29 . Thus, an appropriate selection of transcription-activating CREs is essential for testing repressive elements at-scale in reporter assays for the purpose of understanding their basic mechanisms and impact on disease.…”
Section: Introductionmentioning
confidence: 99%
“…While it has been demonstrated that using stronger promoters in MPRA helps to detect repressive elements, its sensitivity and specificity has not been evaluated systematically 8,27 . In addition, it has been demonstrated that interactions between CREs can exhibit specificity depending on context including the cell-type and TFs involved 28,29 . Thus, an appropriate selection of transcription-activating CREs is essential for testing repressive elements at-scale in reporter assays for the purpose of understanding their basic mechanisms and impact on disease.…”
Section: Introductionmentioning
confidence: 99%